1998
DOI: 10.1111/j.1439-0418.1998.tb01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the entomopathogenic fungus, Beauveria bassiana (Bals), against Aphis crassivora Koch and Bemesia tabaci, Gennandius

Abstract: : Beauveria bassiana as an entomopathogenic fungi showed high effects on the aphid Aphis crassivora and the white fly Bemesia tabaci infesting cucumber. A dose of 1 mg.ml−1 killed 100% of either insects. Lower doses showed lower effects. Nymphs of the two insects were markedly affected by treatment of the fungi. The total duration and the number of survivors were significantly decreased by an increase in the dose of the pathogen. Latent effects were clearly observed in the resulting adults. Adult longevity, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 4 publications
2
15
1
1
Order By: Relevance
“…Total fecundity also showed the same trend to reproductive periods. This result agrees with Zaki (1998) in that the reproductive period and fecundity of cowpea aphid were decreased with an increase of spore dose. An application of entomopathogenic fungi, B. bassiana and V. lecanii, significantly reduced the fecundity of insect pests such as legume flower thrips, lettuce aphid and Russian wheat aphid (Ekesi and Maniania, 2000;Fournier and Brodeur, 2000;Wang and Kundsen, 1993).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Total fecundity also showed the same trend to reproductive periods. This result agrees with Zaki (1998) in that the reproductive period and fecundity of cowpea aphid were decreased with an increase of spore dose. An application of entomopathogenic fungi, B. bassiana and V. lecanii, significantly reduced the fecundity of insect pests such as legume flower thrips, lettuce aphid and Russian wheat aphid (Ekesi and Maniania, 2000;Fournier and Brodeur, 2000;Wang and Kundsen, 1993).…”
Section: Discussionsupporting
confidence: 93%
“…Developmental time at each nymphal stage of cotton aphid was not significantly affected by conidial dose but individual instar periods as well as total nymphal time had a tendency to slightly increase in spore-treated aphids compared with controls treated with 0.001% aqueous Tween 80. These results differ from Zaki (1998) who reported that the nymphal period of A. crassivora was markedly decreased with increasing dosage of B. bassiana.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…However, N. ribisnigri is resistant to some insecticides (Martin et al, 1996;Rufingier et al, 1997;Barber et al, 1999;Dedryver et al, 2010). One alternative to the use of insecticides to reduce the occurrence of this pest is integrated pest management involving the application of entomopathogenic fungi (Dorschner et al, 1991;Zaki, 1998;Steinkraus, 2006;Asman, 2007;Díaz et al, 2010;Scorsetti et al, 2010Scorsetti et al, , 2012Skinner et al, 2012). Fungal pathogens are the most important pathogens of aphids and epizootics are frequently observed that often rapidly reduce aphid populations (Steinkraus, 2006).…”
Section: Introductionmentioning
confidence: 99%